If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -7) + 2(10 + -2x) + 3x = 2x + 1 + 5(x + -9) Reorder the terms: 4(-7 + x) + 2(10 + -2x) + 3x = 2x + 1 + 5(x + -9) (-7 * 4 + x * 4) + 2(10 + -2x) + 3x = 2x + 1 + 5(x + -9) (-28 + 4x) + 2(10 + -2x) + 3x = 2x + 1 + 5(x + -9) -28 + 4x + (10 * 2 + -2x * 2) + 3x = 2x + 1 + 5(x + -9) -28 + 4x + (20 + -4x) + 3x = 2x + 1 + 5(x + -9) Reorder the terms: -28 + 20 + 4x + -4x + 3x = 2x + 1 + 5(x + -9) Combine like terms: -28 + 20 = -8 -8 + 4x + -4x + 3x = 2x + 1 + 5(x + -9) Combine like terms: 4x + -4x = 0 -8 + 0 + 3x = 2x + 1 + 5(x + -9) -8 + 3x = 2x + 1 + 5(x + -9) Reorder the terms: -8 + 3x = 2x + 1 + 5(-9 + x) -8 + 3x = 2x + 1 + (-9 * 5 + x * 5) -8 + 3x = 2x + 1 + (-45 + 5x) Reorder the terms: -8 + 3x = 1 + -45 + 2x + 5x Combine like terms: 1 + -45 = -44 -8 + 3x = -44 + 2x + 5x Combine like terms: 2x + 5x = 7x -8 + 3x = -44 + 7x Solving -8 + 3x = -44 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -8 + 3x + -7x = -44 + 7x + -7x Combine like terms: 3x + -7x = -4x -8 + -4x = -44 + 7x + -7x Combine like terms: 7x + -7x = 0 -8 + -4x = -44 + 0 -8 + -4x = -44 Add '8' to each side of the equation. -8 + 8 + -4x = -44 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = -44 + 8 -4x = -44 + 8 Combine like terms: -44 + 8 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 2x=(360) | | 8-(x+6)=6x-5 | | 2x+y+130=3x+y+160 | | 6x+9=-2x+105 | | 6x+9=-2+105 | | f(81)=74 | | 6y-8-2y+3=0 | | 6n+1=.5 | | (x+y+z)(x+y)-(x-y-z)(x-y)= | | 4+4q=9+3q | | 7*4p-5*3r+3*3q-5*5r+4*5q-10q= | | 3x/4-12=3 | | 2w+1+w=18 | | 0.36(24)+0.04=0.12(6+x) | | 11*11/12-3 | | 8x+4=-2(6x-1) | | y-5=2/4(x-2) | | 7x+5(2+x)=-2 | | (1/3)8 | | 3-4x=2x+25 | | 6x+3=34x+7 | | 23-[3+9y-3(y+3)]=-3(4y-6)-[8(y-1)-10y+13] | | 3(2x+6)+12=-15 | | 5(1-3m)=30-(4m+7) | | 3x-4.9=0 | | x^2-3ax-10a^2=0 | | 7y+6=2y-9 | | 12(3x+4)-5(2x-5)=6x-67 | | 13r+16=5t | | -5-10b=15-11b | | (0.2x+3)(0.2x-3)=0 | | 4[x+2(5-x)]=3x+1 |